2017
DOI: 10.1167/iovs.16-20612
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese Family With Autosomal Dominant Oculocutaneous Albinism Type 4

Abstract: Citation: Oki R, Yamada K, Nakano S, et al. A Japanese family with autosomal dominant oculocutaneous albinism type 4. Invest Ophthalmol Vis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…Using a 3D OCT-2000 (Topcon), Oki et al showed a ganglion cell complex thinning in the temporal region of the fovea, which was noticeably larger in patients with grade 2 than in those with grade 1 FH. Our findings are thus in good accordance with this previous report although the OCT device used and ethnic background of the patients did differ [8]. They found a slight reduction of sensitivity in the nasal visual field, which was not detectable in our cohort and was not a characteristic finding in 15 patients with albinism [15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Using a 3D OCT-2000 (Topcon), Oki et al showed a ganglion cell complex thinning in the temporal region of the fovea, which was noticeably larger in patients with grade 2 than in those with grade 1 FH. Our findings are thus in good accordance with this previous report although the OCT device used and ethnic background of the patients did differ [8]. They found a slight reduction of sensitivity in the nasal visual field, which was not detectable in our cohort and was not a characteristic finding in 15 patients with albinism [15].…”
Section: Discussionsupporting
confidence: 93%
“…The distinct pattern of GCLT temporal to the fovea was also recently reported in a Japanese family with albinism [8]. Using a 3D OCT-2000 (Topcon), Oki et al showed a ganglion cell complex thinning in the temporal region of the fovea, which was noticeably larger in patients with grade 2 than in those with grade 1 FH.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Visual acuity is diminished to varying degrees in most people with OCA, and is caused by refractive errors, colour vision impairment, reduced stereoscopic vision, strabismus, nystagmus and macular (foveal) hypoplasia. Inheritance of OCA is mostly autosomal recessive and caused by pathogenic mutations in multiple genes that encode proteins involved in melanin biosynthesis . Type 1 OCA, associated with mutations in the tyrosinase gene ( TYR ), is the most common type of this disorder in India.…”
mentioning
confidence: 99%
“…Inheritance of OCA is mostly autosomal recessive and caused by pathogenic mutations in multiple genes that encode proteins involved in melanin biosynthesis. 1 Type 1 OCA, associated with mutations in the tyrosinase gene (TYR), is the most common type of this disorder in India. The less common type 4 OCA (MIM 606574), estimated to comprise approximately 10% of all OCA cases in India, is caused by mutations in the solute carrier family 45 member 2 (SLC45A2) gene, also called the membraneassociated transporter protein (MATP) gene.…”
mentioning
confidence: 99%